2018
DOI: 10.1039/c8cc05067h
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(ii)-catalyzed selective C–H difluoroalkylation of aniline derivatives with pyrimidyl auxiliaries

Abstract: A ruthenium-catalyzed alternative para- and meta-difluoroalkylation of anilines is herein reported. The reaction tolerates a broad range of aniline derivatives and provides a convenient approach for accessing the corresponding para/meta-selective difluoroalkylated products. Mechanism studies demonstrated that the initial CAr-H and N-H cycloruthenation is the pivotal step in achieving remote C-H difluoroacetylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Although heteroaromatic compounds are capable of achieving site‐selective fluorinated products because of their intrinsic electronic effects,, general aromatic compounds usually suffer from poor site selectivity,, (Figure a). Until recently, research into site‐selective C−H difluoromethylation of arenes has been of a preliminary nature . For example, the Ackermann group developed a ruthenium‐catalyzed meta ‐selective C−H difluoromethylation of 2‐arylpyridine derivatives .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Although heteroaromatic compounds are capable of achieving site‐selective fluorinated products because of their intrinsic electronic effects,, general aromatic compounds usually suffer from poor site selectivity,, (Figure a). Until recently, research into site‐selective C−H difluoromethylation of arenes has been of a preliminary nature . For example, the Ackermann group developed a ruthenium‐catalyzed meta ‐selective C−H difluoromethylation of 2‐arylpyridine derivatives .…”
Section: Figurementioning
confidence: 99%
“…Until recently,r esearch into site-selective C À Hd ifluoromethylation of arenes has been of ap reliminary nature. [8][9][10] Fore xample,t he Ackermann group developed ar uthenium-catalyzed meta-selective CÀH difluoromethylation of 2-arylpyridine derivatives. [8] A paraselective difluoromethylation of acetanilides and ketoximes by modulating the coordination ability of the directing group was developed by our group.…”
mentioning
confidence: 99%
“…A series of mechanistic studies and DFT calculations suggested that the chelation‐assisted cycloruthenation is the key factor in achieving the para ‐selectivity. Subsequently, Liang and co‐workers reported a similar Ru‐catalyzed para C−H difluoromethylation of pyrimidyl‐protected aniline derivatives [38c] …”
Section: Remote Fluoroalkyl(thiol)ation Reactionsmentioning
confidence: 99%
“…Subsequently, the same group expanded the substrate scope to anilide, indoline and tetrahydroquinoline derivatives under similar conditions [14] . Besides, Liang reported a ruthenium‐catalyzed para‐selective C−H difluoromethylation using pyrimidyl and quinazoline auxiliaries [15] . Moreover, Zhao and Lou further achieved para ‐selective C−H difluoromethylation of electron‐deficient aromatic carbonyls in the presence of palladium catalysts [16] .…”
Section: Introductionmentioning
confidence: 99%